Analisis Korelasi Kerusakan Bangunan Terhadap Tingkat Kepuasan Pengguna Dengan Metode Customer Satisfaction Index (Studi Kasus Gedung F Universitas DR. Soetomo Surabaya) - Nikmatus Sa'adah; Rizki Astri A; Wisnu Abiarto N (AGREGAT, 2024)
Since the construction of building F, Dr. University. Soetomo Surabaya has not experienced any changes either in terms of form or other points of view. Based on observations of the current condition of the building, there is still not enough attention and the age of the building already requires care, maintenance and repair of damage. Building quality greatly influences building user satisfaction because good building quality can make users feel comfortable in the building. The aim of this research is to analyze damaged items, analyze the level of user satisfaction and analyze poor building conditions. The method used in this research is a quantitative method where data collection was carried out by distributing a questionnaire survey via Google Form to 135 respondents consisting of lecturers at the Faculty of Engineering and students using building F, Dr. University. Soetomo Surabaya, apart from distributing questionnaires, this research was carried out by direct observation. This research uses the customer satisfaction index method which aims to determine the level of satisfaction of building users and uses the help of Smart-PLS software to help process data generated from questionnaires by testing its validity and reliability. The results of this research showed several damages, including damage to columns, beams, floor plates, walls, finishing, glass and door frames, floors and ceilings. The damage in this study refers to the classification of building damage according to (PUPR, 2021) where overall damage to walls is categorized as very light damage, damage to columns is categorized as moderate damage, damage to beams is categorized as heavy damage, damage to floor slabs is categorized as heavy damage. , damage to the floor is categorized as light damage, damage to the ceiling is categorized as moderate damage, and for finishing it is categorized as heavy damage due to complete finishing damage. The research results on the level of user satisfaction with building conditions using the customer satisfaction index (CSI) method were 55.41%, which means building users are quite satisfied with the current condition of the building. Apart from that, the results of the condition of the building, according to the respondent's point of view, which were not good were damage to the color of the wall paint, condition of the ceiling, door and window accessories, doors and windows, door and window frames, walls. Keywords: Building Damage, User Satisfaction, Customer Satisfaction Index, Smart-PLS